Blister beetles of genus Epicauta Dejean, 1834 (Coleoptera: Meloidae) from Panamá: diversity, distribution and clinical cases - Roberto J. Miranda; Sergio E. Bermúdez; Emilio E. Romero; Roberto A. Cambra (Gayana)
The blister beetle genus Epicauta Dejean, 1834 from Panamá is revised. The following eight species of Epicauta are recognized for Panamá: E. aragua Adams & Selander, 1979, E. carmelita (Haag-Rutenberg, 1880), E. caustica Rojas, 1857, E. dohrni Haag-Rutenberg, 1880, E. flagellaria (Erichson 1848), E. grammica (Fischer, 1827), E. isthmica Werner, 1949 and E. major Pic, 1924. Information on the species that have caused clinical cases in Panamá is reviewed. An illustrated key to species and distribution in Panamá is included.